Marketing Management of Educational Services in Increasing the Number of Students at MTsN 5 Tanah Datar - Andika Triharnedy Andika; Phen Phen Anoum (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to find out how to plan education services marketing, implement educational services marketing activities and evaluate educational services marketing activities at MTsN 5 Tanah Datar in order to increase the quantity of students. This type of research is qualitative using the case study method. Research data was collected using in-depth interviews and direct observation to the location. The results showed that in planning the marketing of educational services at MTsN 5 Tanah Datar, it was initiated by carrying out a POAC (Planning, Organizing, Actuating and Controlling) which involved teachers, committees and parents in determining the equipment, strategies and programs to be offered. In carrying out the marketing of educational services MTsN 5 Tanah Datar applies an educational services marketing mix consisting of 7P (product, price, place, promotion, person, physical evidence and process) while in promotional activities it is carried out by placing banners, distributing brochures, pamphlets, school websites , Facebook, WhatsApp, and direct visits to Elementary Schools. For evaluation activities on the marketing of education services at MTsN 5 Tanah Datar, the school principal, curriculum representative, student representatives and the team hold a meeting at the end of each month in order to discuss the results obtained and correct what are still deficiencies that must be corrected and strengths that must be maintained